Capital structure, company liquidity, and company size on company value mediated by credit risk - Reza, Ahmad Khairul; Kufepaksi, Mahatma; Jubaedah, Jubaedah (Indonesian Journal of Multidisciplinary Science, 2023)
This study uses quantitative secondary data to determine the effect of capital structure, company liquidity and company size on company value with credit risk as a mediation variable. The researcher used quantitative approach with descriptive quantitative design. The population of this study is banking companies listed on the Indonesia Stock Exchange in the period 2010-2020 totaling 29 banking companies. The data used is a panel data regression method using the eviews version 10 application. Sample selection using full sampling. The results obtained show that (1) Capital structure has a positive effect on company value, (2) Liquidity does not affect company value, (3) Company size does not affect company value, (4) Credit risk does not affect company value, (5) Capital structure has a negative effect on credit risk, (6) Liquidity does not affect credit risk, (7) Company size has a positive effect on credit risk,  (8) Credit risk is not proven as an intervening variable in banking companies in Indonesia.